Dukungan Teman Sebaya dan Coping Religius dalam Mengatasi Stres Akademik Mahasiswa PAI - Linda Anugraeni; Arditya Prayogi; Riki Nasrullah (SURAU : Journal of Islamic Education, 2026)
This study was motivated by the increasing academic stress experienced by students of the Islamic Religious Education (PAI) Study Program, particularly during the final stage of their studies due to academic demands, thesis completion, graduation targets, and social pressures. The study aimed to describe the forms of academic stress experienced by the 2022 cohort of PAI students at UIN K.H. Abdurrahman Wahid Pekalongan and to examine the role of peer support in strengthening their religious coping strategies. The novelty of this study lies in its examination of the relationship between peer support and religious coping within the context of Islamic Religious Education students, thereby viewing academic stress not only from psychological perspectives but also from social and spiritual dimensions. This study employed a qualitative approach with a phenomenological design. Data were collected through interviews, observations, and documentation involving ten participants, consisting of five students experiencing academic stress and five of their peers. The findings indicate that academic stress is characterized by anxiety, overthinking, sleep disturbances, fatigue, panic, and decreased learning focus and academic performance, resulting from both internal and external factors. Peer support, provided through emotional, informational, instrumental, and companionship support, was found to strengthen religious coping through prayer (ṣalāh), dhikr (remembrance of God), supplication (du‘ā’), patience, trust in God (tawakkul), and personal effort (ikhtiar). These findings highlight the importance of developing a collaborative, religious, and peer-supported academic ecosystem to promote students' psychological well-being and academic persistence.